THE RIGHT TO BE FORGOTTEN IN BRAZIL FROM THE THEME 786/STF: AN HERMENEUTIC INVESTIGATION ON JUDGEMENT OF THE EXTRAORDINARY APPEAL Nº 1.010.606 (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
The present article seeks to investigate the (im)possibility of recognition of right to be forgotten in the sphere of Brazilian constitutional-procedural jurisdiction, notably with regard to the judgment of Extraordinary Appeal 1.010.606, with general repercussion, which gave rise to Theme 786 of Supreme Federal Court. For this, the essay is subdivided into two main sections. It begins by investigating the elements that make up the votes of the aforementioned decision, such as personality rights, oblivion and freedom of expression. The second chapter, in turn, focuses on the hermeneutic understanding of the arguments present in the votes of STF’s justices that delineated the decision and the consequent edition of Theme 786 of the Supreme Court. Thus, as a research problem, the question is: to what extent is it possible to understand the final decision of RE 1.010.606 as constitutional and hermeneutically adequate? To solve the problem raised, a phenomenological-hermeneutic approach is used. At the end of the work, it is possible to understand that the thesis established in the judgment of Extraordinary Appeal 1,010,606 respects the coherence, integrity and autonomy of law and, therefore, can be considered hermeneutically and constitutionally correct.